Effectiveness Of Civil Judgment Execution In The Semarapura District Court - Wulantrisna, A.A. Sagung Yuni; Wiratny, Ni Ketut; Sihotang, Erikson (Al-Makki Publisher, 2025)
The execution of civil court decisions is a decisive stage in the enforcement of justice and serves as a test of the effectiveness of the judicial system. This study aims to analyze the effectiveness of the execution of civil judgments at the Semarapura District Court using an empirical juridical approach. The results show that although the legal basis and execution procedures are clearly regulated, their implementation in practice still faces various obstacles. Data from 2022–2024 indicate that only a portion of execution requests are successfully implemented, while the rest fail or are withdrawn due to structural, substantial, and cultural barriers. Key challenges include the limited number of bailiffs, insufficient supporting facilities, unclear court orders, changes in the status of disputed objects, and strong community resistance rooted in local customs and kinship values. The Semarapura District Court has made several efforts, such as increasing coordination with security forces, involving community leaders, providing bailiff training, and digitizing administration. Ultimately, the effectiveness of execution depends on the synergy between legal substance, institutional structure, legal culture, supporting facilities, and the level of legal awareness in society. Multi-stakeholder collaboration is needed to ensure that law enforcement through civil execution is effective, fair, and socially harmonious.